Handbook of product graphs - 511964 Hammack, Richard H.; Imrich, Wilfried, 1941-; 1962-; Imrich, Wilfried, 1941- Product graphs, structure, and recognition (Boca Raton, FL : CRC Press)
Includes bibliographical references and indexes.